In-situ fabrication of gold nanoparticle functionalized probes for tip-enhanced Raman spectroscopy by dielectrophoresis - Sweetenham, Claire Sue; Woolley, Richard; Notingher, Ioan (Society of Photo-optical Instrumentation Engineers, 2016)
We report the use of dielectrophoresis to fabricate in-situ probes for tip-enhanced Raman spectroscopy (TERS) based on Au nanoparticles. A typical conductive atomic force microscope (AFM) was used to functionalize iridium-coated conductive silicon probes with Au nanoparticles of 10-nm diameter. Suitable TERS probes can be rapidly produced (30 to 120 s) by applying a voltage of 10 Vpp at a frequency of 1 MHz. The technique has the advantage that the Au-based probes are ready for immediate use for TERS measurements, minimizing the risks of tip contamination and damage during handling. Scanning electron microscopy and energy dispersive x-ray spectroscopy were used to confirm the quality of the probes, and used samples of p-ATP monolayers on silver substrates were used to demonstrate experimentally TERS measurements.